PERANAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN PETANI TANAMAN PADI (Oryza Sativa) - Mahfuds Shidiq; Khusnul Khotimah, M. Dini Adita (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Indonesia is an agricultural country that can meet the food needs of its people with its agricultural products. In terms of meeting the food needs of the community from agricultural products, it can be said that farmers have a very important role in meeting the food needs of the community. The Mandiri Sejati Farmers Group, Bulakamba District, Brebes Regency, a farmer group consisting of Pakijangan village residents who are engaged in agriculture, plantations and agribusiness. However, behind successful farmers there are tips for becoming farmers who are able to process their farming businesses to become successful farmers and increase community income. The research method and data analysis method used several data collection techniques including 1. Primary and secondary data sources 2. Data collection techniques 3. Sample Determination 4. Data Analysis. Data were obtained from observations and interviews with members of the True Independent Farmers Group. The results of field research show that farmer groups play a very important role in agricultural development, especially in increasing rice production in Pakijangan Village. The role of farmer groups as a learning class and a means of cooperation between groups is categorized as high with an average as a learning class of 2.47 and as a means of cooperation between groups of 2.52. While the role of the ani group as a production unit is categorized as medium with an average of 2.24